Pheochromocytomas and paragangliomas: assessment of malignant potential. - Korevaar, T; Grossman, AB (2011)
Pheochromocytomas and paragangliomas (PPGLs) are rare catecholamine-secreting tumors which arise from the adrenal glands or sympathetic neuronal tissue. Malignant transformation of these tumors occurs in a significant proportion and may therefore lower overall survival rates. In patients with PPGLs it is impossible to identify malignant disease without the presence of metastatic disease, something which can occur as long as 20 years after initial surgery. Early identification of malignant disease would necessitate a more aggressive treatment approach, something which may result in better disease outcome. We have therefore reviewed possible predictors of malignancy and current developments in order to help clinicians to swiftly assess malignant potential in patients with PPGLs. Currently, there is no absolute marker which can objectively reflect malignant potential. Tumor size is the most reliable predictor and should therefore be used as the baseline characteristic. The combination of various clinical markers (extra-adrenal disease and post-operative hypertension), biochemical markers (high dopamine, high norepinephrine and epinephrine to total catecholamine ratio) and/or histological markers (SNAIL, microRNAs and/or microarray results) can raise or lower the suspicion of malignancy. Furthermore, we discuss how clinical markers may affect biochemical results linked to malignancy, how biochemical results may distinguish hereditary syndromes, the role of imaging in determining malignant potential and tumor detection, and recent results of proposed histological markers.